JAN PAWEŁ II O KOBIECIE - Gałkowski, Jerzy W. (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The anthropology of John Paul II is a synthesis of his philosophical and theological considerations. Karol Wojtyła’s central anthropological issues focus on the analysis of humanity, human nature, and person, with consciousness and causality as the basis for the agency of human person. These issues also underlie his considerations over the realization of humanity in a woman and man, their mutual relationships, as well as the values that define them or result from them. The relationships analyzed by John Paul II reach far beyond ontology or the mode of existence (although take their root in these), towards more “mundane” problems which are, however, still important in everyday life; issues such as family life, living alone, work, economy or economics. The pope devoted a number of documents to the question of women. In his “Letter to women” (1995), he mentions all the modes of a woman’s life: being a mother, spouse, daughter, sister, a professionally working-woman, or a consecrated woman. The recognition of the woman’s dignity relates to all and each individual woman. John Paul II emphasizes that the woman has had impact on human history equal to that of the man. The common being of the man and the woman consists in their being in a mutual relationship with each other. It is the relationship of being “next to one another”, “together with one another”, as well as “one for another”. It is important to notice the unity of a human – both the man and the woman – the unity with many aspects and layers. The unity and equality of sexes does not imply their identity, nor does it deny some level of differences between their tasks. When speaking of the equality and mutuality of the relationships between sexes, one needs to add that it is not only the woman who is obliged by love of the man, but it is also the man who is obliged by the woman’s words of love. It can be clearly seen in the fate of many women, and their relationship with men. I mean here sexual abuse of women (but also of children) by men. This requires special understanding. Admitting that love and respect to each person are fundamental values is a proper direction to be taken in the considerations over culture.